2013
DOI: 10.1002/lt.23706
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein and modified response evaluation criteria in Solid Tumors progression after locoregional therapy as predictors of hepatocellular cancer recurrence and death after transplantation

Abstract: Locoregional therapy (LRT) is being increasingly used for the management of hepatocellular cancer (HCC) in patients listed for liver transplantation (LT). Although several selection criteria have been developed, stratifications of survival according to the pathology of explanted livers and pre-LT LRT are lacking. Radiological progression according to the modified Response Evaluation Criteria in Additional Supporting Information may be found in the online version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
175
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(190 citation statements)
references
References 42 publications
8
175
0
7
Order By: Relevance
“…In selection criteria for LT, the biological behavior of the tumor is replacing the size/number concept used by most of centers. [30][31][32] This study proved that even the biological behavior of the primary tumor has an impact on the outcome of the management of recurrent HCC. This should be a motive for further studies with larger cohorts of patients to evaluate the impact of pathological criteria of primary resected HCC and the characteristics of NTLP on the outcome of management of IHR, attempting for proper procedure/patient matching.…”
mentioning
confidence: 59%
“…In selection criteria for LT, the biological behavior of the tumor is replacing the size/number concept used by most of centers. [30][31][32] This study proved that even the biological behavior of the primary tumor has an impact on the outcome of the management of recurrent HCC. This should be a motive for further studies with larger cohorts of patients to evaluate the impact of pathological criteria of primary resected HCC and the characteristics of NTLP on the outcome of management of IHR, attempting for proper procedure/patient matching.…”
mentioning
confidence: 59%
“…Although the numbers are small, this observation highlights the importance of change in AFP in the context of LRT while on the LT waiting list as Lai et al 5 have indicated from their recent multicenter study. We agree that there should be a "dynamic" approach to using AFP in the selection guidelines for LT that are readily adoptable in clinical practice.…”
Section: To the Editorsmentioning
confidence: 70%
“…Such slope was able to strongly predict post-LT recurrence, and microvascular invasion [24] . Finally, the European multicenter experience (EURHECALT study) performed on 306 patients meeting and 116 exceeding MC showed that mRECIST progression during waiting time and AFP slope > 15 ng/mL per month were the sole predictors of tumor recurrence and post-LT death [25] . All the reported studies are reassumed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Vibert et al [23] adopted the value obtained from the difference between the lowest and highest measured divided by the lapse of time passed between the two measurements; our group (Lai et al [25] ) adopted the measures at the moment of waiting-list inscription and at moment of LT. Both methods insufficiently show the real behavior of AFP changes overtime because they are not able to completely capture the AFP oscillations during the time.…”
Section: Resultsmentioning
confidence: 99%